표고 및 구름버섯으로부터 Mn - peroxidase 와 Laccase 의 생산 - 배현종; Hyeun Jong Bae; 한옥수; Ok Soo Han; 고홍범; Hong Bum Koh; 김윤수; Yoon Soo Kim (목재공학, 1993)
This study was undertaken to investigate the characteristics and the productivities of lignin olytic enzymes: laccase (Lac) and Mn-dependent peroxidase (MnP) from Coriolus versicolor and Lentinus edodes respectively. Enzymes were isolated from cultural filterates and purified according to the standard methods. These enzymes showed one band in SDS-PAGE and their molecular weights were found 62,000 and 45,000 dalton respectively. Polyclonal antibodies against Lac and MnP were raised against mouse. In the ELISA (enzyme-linked immunosorbent assay), Lac and MnP-antiserum produced a strong positive reaction with Lac and MnP antigen($A_{405}$=2.50 and 3.53 respectively). The sera to negative (S/N) ratio was determined by the dividing the mean absorbance of antibodies by the corresponding diluted samples from normal mouse serum. The sera produced showed 2 times more positive reaction in S/N ratio than negative sera.